2016
DOI: 10.17507/jltr.0705.25
|View full text |Cite
|
Sign up to set email alerts
|

Philosophy-based Language Teaching Approach on the Horizon: A Revolutionary Pathway to Put Applied ELT into Practice

Abstract: Abstract-As a unique approach in today's language teaching methodology, Philosophy-based Language Teaching (PBLT) engages learners in dialogues using philosophical question and answer activities to tackle the process of language learning in ELT classes. Accordingly, the present study sought to illuminate the practical ways through which PBLT could be utilized to put Applied ELT into practice. In so doing, the key is to redefine the inherent roles of both English learners and practitioners in an Applied ELT cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Finally, more recently, the study by Hemmati and Hoomanfard (2014), reported in Dabbagh and Noshadi (2016), shows that applying the PBLT approach in the EFL classroom can improve the students' speaking skill and their willingness to communicate. The authors of the same study concluded that the observed effectiveness of PBLT in improving the students' speaking skill and their willingness to speak is a sign that PBLT could be the alternative approach to the traditionally used IRF (Initiation-Response-Follow up) approach in teaching the speaking skill.…”
Section: On the Effectiveness Of Pblt In Efl Instructionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, more recently, the study by Hemmati and Hoomanfard (2014), reported in Dabbagh and Noshadi (2016), shows that applying the PBLT approach in the EFL classroom can improve the students' speaking skill and their willingness to communicate. The authors of the same study concluded that the observed effectiveness of PBLT in improving the students' speaking skill and their willingness to speak is a sign that PBLT could be the alternative approach to the traditionally used IRF (Initiation-Response-Follow up) approach in teaching the speaking skill.…”
Section: On the Effectiveness Of Pblt In Efl Instructionmentioning
confidence: 99%
“…Consequently, a new theoretical approach to EFL classroom practices was needed. It is in that perspective that the PBLT, which "engages learners in dialogues using philosophical questions and answer activities to tackle the process of language learning in ELT classes", came as an application tool of Applied ELT in EFL contexts (Dabbagh & Noshadi, 2016, p. 1022. As was observed by Shahini and Riazi (2011), EFL learners become automatically ready and motivated to participate in classroom discussions whenever a philosophical question is raised.…”
Section: Literature Review Pblt Explainedmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the main area of focus has been of identification of sexism and gender representations in ELT/EFL textbooks. Dabbahg and Noshadi (2016), Craeynest (2015), Hall (2014), Lee (2014), Lee and Collins (2008) have been generally carried out on firstness, omission, visibility linguistic biases in the selection of nouns and adjectives associated with each gender. These studies have found gender biases in textbooks and have recommended fair representation of female gender by the authors.…”
Section: Theoretical Frameworkmentioning
confidence: 99%